Low intensity ultrasound-induced apoptosis in human gastric carcinoma cells - Feng, Yi (The WJG Press and Baishideng, 2008)
AIM: To investigate the low intensity ultrasound (US)-induced apoptosis in human gastric carcinoma cells and its potential mechanism and to suggest a new therapeutic approach to gastric carcinoma. METHODS: Human SGC-7901 gastric carcinoma cells were cultured in vitro and irradiated by low intensity US for 10 min at different intensities with different incubation times after irradiation. Morphologic changes were examined under microscope with trypan blue staining and then the percentage of early apoptotic cells was detected by flow cytometry (FCM) with double staining of fluorescein isothiocyanate (FITC)-Annexin V/propidium iodide (PI). Two-dimensional electrophoresis (2DE) was used to get the protein profile and some proteins differently expressed after US irradiation were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). Functional analysis was performed to investigate the mechanism of US-induced cell apoptosis. RESULTS: The percentage of apoptotic cells increased about 10% after US irradiation (12.0 W/cm(2), 12 h culture). The percentage of early apoptosis and secondary necrosis in the US-irradiated cells increased with the increased US intensity. Moreover, apoptotic cells increased with the increased culture time after US irradiation and reached its maximum at about 12 h. Several new proteins appeared after US irradiation and were up or down regulated more than 2 times. Some heat shock proteins (HSPs) were found to be associated with the signal process simulating the apoptosis of cells. CONCLUSION: Low intensity US could induce apoptosis in human gastric carcinoma cells. US-induced apoptosis is related to US intensity/culture time. US-induced apoptosis may be caspases-dependent and endoplasmic reticulum (ER) stress-triggered apoptosis may also contribute to it. Proteomic experimental system is useful in finding the protein alteration in carcinoma cells after US irradiation, helping to develop a new cancer therapy.